2014
DOI: 10.1080/14780887.2014.955224
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Template Analysis in Qualitative Psychology Research

Abstract: Thematic analysis is widely used in qualitative psychology research, and in this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
959
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,215 publications
(969 citation statements)
references
References 38 publications
5
959
0
5
Order By: Relevance
“…The study was designed and developed with Sands, who have extensive experience of providing support to bereaved families, thus providing extra assurance that the study was conducted in an ethical manner. Template Analysis afforded the opportunity to develop a priori codes based on extant literature, but also ensured that emerging themes were identified (Brooks et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study was designed and developed with Sands, who have extensive experience of providing support to bereaved families, thus providing extra assurance that the study was conducted in an ethical manner. Template Analysis afforded the opportunity to develop a priori codes based on extant literature, but also ensured that emerging themes were identified (Brooks et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The qualitative data was analysed using Template Analysis (Brooks, McCluskey, Turley, & King, 2015). This method is a flexible but structured approach to data analysis, which allows for integration of a priori codes and emerging themes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A technique called template analysis was used to analyse the transcripts. Template analysis involves the use of a coding template which is generated either a priori or from a preliminary analysis of a subset of the data (Brooks, McCluskey, Turley, & King, 2015). The coding structure in this study was a priori identified and comprised characteristics A1 to E4 of high reliability project organising as posited by Saunders (2015).…”
Section: Methodsology and Methodsmentioning
confidence: 99%